2018
DOI: 10.1002/anie.201805752
|View full text |Cite
|
Sign up to set email alerts
|

PNA Hybrid Sequences as Recognition Units in SNARE‐Protein‐Mimicking Peptides

Abstract: Membrane fusion is an essential process in nature and is often accomplished by the specific interaction of SNARE proteins. SNARE model systems, in which SNARE domains are replaced by small artificial units, represent valuable tools to study membrane fusion in vitro. The synthesis and analysis is presented of SNARE model peptides that exhibit a recognition motif composed of two different types of peptide nucleic acid (PNA) sequences. This novel recognition unit is designed to mimic the SNARE zippering mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Third, the fusion kinetics obtained from in vitro reconstitution assay using the SNAREs alone is not comparable to that observed in vivo . In addition, previous studies reported that two complementary paired nucleic acid strands linked by the TMRs of syntaxin‐1 and synaptobrevin‐2 could mediate in vitro liposome fusion as well [ 65 , 66 ]. Another study revealed that artificial coiled‐coil peptides linked by the JLRs and TMRs of the SNAREs could induce liposome fusion[ 67 ].…”
Section: Neuronal Snare Complex Assemblymentioning
confidence: 99%
“…Third, the fusion kinetics obtained from in vitro reconstitution assay using the SNAREs alone is not comparable to that observed in vivo . In addition, previous studies reported that two complementary paired nucleic acid strands linked by the TMRs of syntaxin‐1 and synaptobrevin‐2 could mediate in vitro liposome fusion as well [ 65 , 66 ]. Another study revealed that artificial coiled‐coil peptides linked by the JLRs and TMRs of the SNAREs could induce liposome fusion[ 67 ].…”
Section: Neuronal Snare Complex Assemblymentioning
confidence: 99%
“…In the present study, different conditions for bulk leaflet mixing assays performed with established SNARE‐like model peptides are inspected and evaluated. The model peptides either contain peptide nucleic acid (PNA) 6 or coiled‐coil forming peptide segments (E3/K3) 7 as recognition units (Table 1). Both structural motifs have already been used in earlier studies to explore membrane fusion 8,9 .…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of liposomes as well as the bulk leaflet mixing assays were performed as described earlier. 6,7 In brief, solutions of the respective lipids and peptides were mixed and the organic solvents were evaporated to obtain lipid films. The lipid films were rehydrated in buffer and proteoliposomes were formed by extrusion.…”
Section: Resultsmentioning
confidence: 99%
“…Beginning in the mid-1990s, scientists have explored the properties of a class of PNAs termed alanyl nucleic acids (ANAs). As opposed to dipeptide-based PNA structures, in which a nucleobase is attached to every other amino acid to match the six-atom backbone repeat geometry found in RNA and DNA, ANA contains a nucleobase-substituted amino acid at every position in the sequence (Chart ). Amino acids are present in ANA with alternating chiral configurations.…”
Section: Peptide Interactions With Nucleic Acidsmentioning
confidence: 99%